Identification of climatically suitable Ethiopian training sites to prepare marathon runners for the 2020 Olympic Games - Perumal, J. S. R.; Islam, Z.; Siddharam, H. S. (New Studies in Athletics, 2017)
Competing in the marathon in warm weather negatively impacts performance and challenges the thermoregulation System of the runner. With increasing tem- perature and humidity, running velocity decreases. Runners training for top-level races such as the Olympic Games will include acclimatisation to the expected climatic conditions of the event as a part of their preparations. Acclimatisation is of particular interest for marathon runners aspiring to success at the 2020 Olympic Games in Tokyo, where the temperature and humidity in the Games period - late July to early August - are expected to be uncomfortably high. The aim of this study was to identify climatically suitable sites in Ethiopia for training marathon runners focused on Tokyo. Weather data of Ethiopia and Tokyo were collected from the global weather web portal of the University Texas, USA. To extract the similar weather condition in Ethiopia, weather data in point's vector format was first converted into Raster format with GIS (IDW) techniques. Thereafter, Tokyo's weather was extracted from Raster data using conditional Statements with a Raster calculator. As a resuit, the authors identified suitable areas across the country for each month of the year and four sites suitable for year-round training.